Data interpolation using Runge Kutta method - Karim, S.A.A. (American Institute of Physics Inc., 2018)
Runge Kutta (RK) is a famous method that can be used to solve differential equation with initial value problems (IVP). There are many variants for RK method. For instance, the most widely used are RK4 and RK5 where 4 and 5 stands for the order of the RK methods. Data interpolation are important in many engineering applications. Usually for data interpolation, the interpolant must interpolate the data set and the first derivatives. This study discusses the application of RK4 for data interpolation by interpolating the data through cubic spline interpolation i.e. RK4-CS method. Several numerical findings will be presented including comparison with some established schemes such as cubic spline. From our findings, RK4 is suitable for data interpolation with higher degree of accuracy. Â© 2018 Author(s).